Comparative Study of In-service Teacher Education between China and Germany - Ye Zhang; Chunwen Hao (ÜNİVERSİTEPARK Limited, 2016)
This paper aims to point out the insufficiencies of in-service teacher education in China and Germany, and correspondingly provide suggestions for enhancing teacher's quality and quantity effectively to fit the higher requirements of school education. In this study, in-service teacher education in China and Germany are discussed through a qualitative analysis. This paper resolves the following issues through the comparison of in-service teacher education between China and Germany: (1) Exploration of similarities and differences of the institutions, aims, and modes of in-service education of the two countries. (2) Analysis of the educational management measures between the two countries; finding the advantages of these measures to improve the teachers' quality and quantity. These measures include systems of admission, appointment, treatment, and assessment. (3) Point out the problems of teacher education in China and Germany, and correspondingly give some suggestions to improve on inadequacies. This paper fulfills an identified need to improve new teachers' professional development through transforming previous studies with teaching experience in real educational situations.